ESGE Days 2019 2019
DOI: 10.1055/s-0039-1681724
|View full text |Cite
|
Sign up to set email alerts
|

Ercp in Infants, Children, and Adolescents – Different Roles of the Methods in Different Age Groups

Abstract: BackgroundEndoscopic retrograde cholangiopancreatography (ERCP) is seldom used in children, and published series have limited numbers of pediatric patients. The aim of this retrospective observational study was to assess the efficacy and safety of pediatric ERCP in a large group of children. MethodsData were evaluated from 626 children with biliopancreatic disorders admitted to University Hospital Motol, Prague, between January 1999 and January 2018. Clinical data were obtained by retrospective evaluation of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 13 publications
3
8
0
Order By: Relevance
“…The complication rate of ERCP in children is around 10 % [3]. Our pooled complication rate was similar to that in previous re-ports [18,21].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The complication rate of ERCP in children is around 10 % [3]. Our pooled complication rate was similar to that in previous re-ports [18,21].…”
Section: Discussionsupporting
confidence: 86%
“…Technical success for diagnostic and therapeutic ERCP in children is high, as in adults [8,18]. In children, ERCP should be more challenging, but complication rates in studies are similar to those reported in adults when performed by expert endoscopists [4].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Several centers no longer have an infant ERCP duodenoscope due to breakdowns and wear [ 15 ]. If the production of these endoscopes is not restored, the diagnostic and therapeutic role of ERCP in neonates and infants will be endangered [ 16 ].…”
Section: Discussionmentioning
confidence: 99%